Research Writing, Peer Review and Academic Publishing: Benefits of Individual, Institutional and Journal Mentoring - Mahayosnand, Ponn P. (GILE Journal of Skills Development, 2024)
Writing academic research papers acceptable for journal publication is not often taught in graduate programs let alone in undergraduate studies. Students and early career researchers (herein known as students for both categories) usually undergo a trial-and-error period to learn how to navigate the publication submission process—a long and daunting task. However, E-mentoring, or electronic mentoring, has proven to be beneficial for students. E-mentoring opportunities can be found by a pro-active student seeking out published researchers in their fields and requesting if they can mentor them. Colleges, universities or other academic institutions may have formal or informal research or peer review programmes, internship, field experience or practicum courses for-credit. Academic journals may also host student mentoring programmes for peer review, editing, and/or research writing hands-on experiences. Mentoring students in research writing and the journal publication process should start as early in one’s academic career as possible. Age or academic status should not be seen as a deterrent or disadvantage when mentored by a patient, experienced and enthusiastic research mentor. Such e-mentoring experiences can be offered by individual researchers, at the institutional level or from the academic journal—the latter being the most ideal model worthy of advocacy and replication.